2015
DOI: 10.12669/pjms.312.6049
|View full text |Cite
|
Sign up to set email alerts
|

Study on relationships among deep vein thrombosis, homocysteine & related B group vitamins

Abstract: Objectives:Hyperhomocysteinemia has been considered as a potential risk factor for deep venous thrombosis (DVT) but it is still controversy. We aimed to evaluate the prevalence of hyperhomocysteinemia in patients with DVT. Our second objective was to document the prevalence of folate, Vitamin B6, and Vitamin B12 level in this patient population.Methods:Sixty patients with DVT aged from 23 to 84 years, were assessed regarding demographic characteristics, serum levels of homocysteine, folate, vitamin B12, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
1
22
1
2
Order By: Relevance
“…It is biosynthesized from the amino acid methionine to which it can also be recycled in a process that involves folate and various B-vitamins (B6 and B12). When the upstream or downstream metabolic pathway of HCY is blocked or delayed for various reasons, it leads to the accumulation of HCY, causing hyperhomocysteinaemia which, although causing no symptoms, affects the interior lining of blood vessels, increasing the risk of atherosclerosis (Sun et al 2017); increases the risk of deep vein thrombosis (Kamat et al 2010, Ekim et al 2015 and pulmonary embolism (Cellai et al 2014); may be related to Alzheimer's disease (Sharma and Lipincott 2017) and other types of dementia (Xie et al 2017) and may be associated with pre-eclampsia in pregnancy (Sayyah-Melli et al 2016, Wadhwani et al 2016. Thus, hyperhomocysteinaemia is associated with various diseases, in particular CVD (Olkkonen 2012, Lathe et al 2014.…”
Section: Homocysteine (Hcy)mentioning
confidence: 99%
“…It is biosynthesized from the amino acid methionine to which it can also be recycled in a process that involves folate and various B-vitamins (B6 and B12). When the upstream or downstream metabolic pathway of HCY is blocked or delayed for various reasons, it leads to the accumulation of HCY, causing hyperhomocysteinaemia which, although causing no symptoms, affects the interior lining of blood vessels, increasing the risk of atherosclerosis (Sun et al 2017); increases the risk of deep vein thrombosis (Kamat et al 2010, Ekim et al 2015 and pulmonary embolism (Cellai et al 2014); may be related to Alzheimer's disease (Sharma and Lipincott 2017) and other types of dementia (Xie et al 2017) and may be associated with pre-eclampsia in pregnancy (Sayyah-Melli et al 2016, Wadhwani et al 2016. Thus, hyperhomocysteinaemia is associated with various diseases, in particular CVD (Olkkonen 2012, Lathe et al 2014.…”
Section: Homocysteine (Hcy)mentioning
confidence: 99%
“…A few other studies also shown higher mean values of serum Homocysteine in DVT patients as compared to controls but they found no significant association between serum Homocysteine levels and DVT [17] [18]. In a study done by E Kim et al reported that 43.3% patients with low folic acid concentration along with Hyperhomocysteinemia [19]. Souheil et al conducted a study on patients with DVT and concluded that Hyperhomocysteinemia is independently associated with DVT and Homocysteine levels should be assessed in patients with DVT and effect of vitamin B6 and B12 and folic acid supplementation should be tested among them [12].…”
Section: Discussionmentioning
confidence: 96%
“…In the study done by E Kim et al patients with Hyperhomocysteinemia, vitamin B12 and folic acid therapy should be recommended which will lower the Homocysteine levels and may help in reducing the recurrence of DVT [19].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of hemostasis as an independent risk factor for venous thrombosis still remain controversial. Previous studies have presented the relationships between homocysteine and deep vein thrombosis (18,19). The correlation of homocysteine and vascular thrombosis disease has been investigated in several clinical studies that demonstrated an increasing plasma total homocysteine (20,21).…”
Section: Introductionmentioning
confidence: 99%